PENINGKATAN KETERAMPILAN ANALISIS PUISI DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) DALAM PEMBELAJARAN BERDIFERENSIASI DI SMAN 14 SEMARANG (psnppg, 2024)
The research method used is a quantitative method. Research methods and techniques were carried out using questionnaire methods on Google Form media and observation methods in the implementation of learning. The results of the research describe that the application of the Teaching at The Right Level (TaRL) approach in differentiated learning experiences an increase in learning outcomes in each cycle. Learning outcomes in cycle I obtained an average value of 76.9 and increased to 83.8 in cycle II
Keywords: enhancement; differentiated learning; TaRL